Acid-alkali resistant paint, acid-alkali resistant coating, preparation method and application thereof

Through the blending of liquid fluoroelastomer, epoxy acrylic resin oligomer and nanographyne functionalized mesoporous tungsten carbide, and the radiation cross-linking curing technology is used to form an integrated coating material, solving the problems of VOC emissions, heavy mass and narrow anti-corrosion fields of existing acid- and alkali-resistant coatings, achieving lightweight, pollution-free and widely applicable anti-corrosion effects.

CN117089284BActive Publication Date: 2025-04-08YANGZHOU CIMC TONGHUA SPECIAL VEHICLES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311081406.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-04-08
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

The existing acid-base resistant coatings have problems with VOC emissions, heavy mass and narrow anti-corrosion fields, and it is difficult to meet the wide range of lightweight, pollution-free and anti-corrosion media.

Method used

The mesoporous tungsten carbide blend is used to blend liquid fluoroelastomer, epoxy acrylic resin oligomer and nanographyne functionalized mesoporous tungsten carbide, and an integrated coating material is formed through irradiation cross-linking curing technology to improve the hardness, impact resistance and corrosion resistance of the coating.

Benefits of technology

It has achieved low VOC emissions and lightweight coatings, which are widely used in multiple anticorrosion fields such as acid and alkali, and has improved the hardness, impact resistance and corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117089284B_ABST
    Figure CN117089284B_ABST
Patent Text Reader

Abstract

The present invention discloses an acid- and alkali-resistant paint, an acid- and alkali-resistant coating, and a preparation method and application thereof. The preparation method of the paint comprises the following steps: blending liquid fluororubber, epoxy acrylic resin polymer, and nano-graphene-functionalized mesoporous tungsten carbide in a weight ratio of (2-4): 1: (0.06-0.1) to obtain. In the acid- and alkali-resistant paint of the present invention, the functional groups brought by the epoxy resin of the epoxy acrylate can improve the adhesion of the fluororubber before and after curing; Graphene can enhance the overall anti-corrosion ability of the coating material; and mesoporous tungsten carbide can greatly increase the hardness of the coating. The present invention selects nano-graphene-functionalized mesoporous tungsten carbide, and the tungsten carbide is fixed in series by Graphene to solve the problem of coagulation of inorganic materials. The triple bonds in Graphene, the double bonds in the fluororubber, and the double bonds in the epoxy acrylic resin polymer can undergo free radical polymerization, so that the three are not simply physically blended, but form an integrated coating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-corrosion coating, and in particular to an acid- and alkali-resistant coating, an acid- and alkali-resistant coating, and a preparation method and application thereof. Background Art

[0002] Traditional tanks used to transport chemicals are mainly lined with PE (polyethylene). The inner wall of the tank is protected by heating PE and cooling it to prevent the chemicals in the tank from being affected by the external environment, while preventing chemical leakage from causing harm to the environment and human body. PE linings are widely used in the chemical, pharmaceutical, food, metallurgical and other industries. However, the preparation process of PE linings is complex, inefficient, and heavy, which not only increases transportation costs, but also fails to meet the current demand for lightweight passenger cars and transport vehicles.

[0003] Currently, the main methods of corrosion protection in transport tanks that replace PE lining technology on the market include solvent-based paints / coatings, water-based paints / coatings, UV coatings / coatings, etc.

[0004] Solvent-based paint / coating is a volatile paint made by mixing, stirring, dissolving and grinding a certain amount of pigments, fillers and additives with polymer synthetic resin as the main film-forming substance and organic solvent as the diluent. After being applied on the substrate, as the solvent contained in the paint evaporates, the film-forming substance and other non-volatile components together form a uniform and continuous film, i.e., the coating. Because the coating film is relatively tight, it usually has good hardness, gloss, water resistance, acid and alkali resistance, good weather resistance, and pollution resistance. However, due to the volatilization of a large amount of organic solvents during construction, it is easy to pollute the environment.

[0005] Water-based paint / coating uses water as a solvent, which is very effective in reducing pollution and saving resources. The tools used for painting can be cleaned with water, which greatly reduces the harm to construction workers. It can be directly applied on wet surfaces and in humid environments, has good adaptability to material surfaces, and has strong coating adhesion. However, due to a series of defects after water-based coating, water-based paint / coating cannot be used for heavy-duty corrosion protection, resulting in more restrictions on the medium for transportation.

[0006] UV paint / coating has a fast curing speed, and cross-linking curing is completed almost instantly, so the production efficiency is very high. The solid content of UV paint is very high, which can reach 100%, so UV paint has no volatile components and will not pollute the environment. The coating of UV paint has high hardness and good wear resistance. It is also resistant to acids and alkalis, salt spray, and gasoline, and the coating of UV paint has good gloss. Although UV paint / coating can solve some problems of solvent-based and water-based paint / coating, UV paint / coating contains photoinitiators, which are easy to migrate. During transportation, the photoinitiator that migrates to the surface will have the risk of reacting with the medium, causing property and personal safety losses to customers and transportation personnel. Summary of the invention

[0007] In view of the current problems of VOC emissions, heavy weight and narrow anti-corrosion range of acid and alkali resistant coatings, the present invention provides an acid and alkali resistant coating, an acid and alkali resistant coating and a preparation method and application thereof, which can simultaneously meet the needs of lightweight, pollution-free and a wide range of anti-corrosion media.

[0008] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing an acid- and alkali-resistant coating, which comprises the following steps: blending liquid fluororubber, epoxy acrylic resin polymer and nano-graphene functionalized mesoporous tungsten carbide in a weight ratio of (2-4):1:(0.06-0.1) to obtain.

[0009] In the above technical solution, the functions of each component are as follows:

[0010] Liquid fluororubber: In addition to excellent chemical resistance and heat resistance, fluororubber is also homogeneous, with no problems such as penetration, cracking and pinholes on the surface. These characteristics can improve sealing performance, extend the operating cycle, and effectively reduce maintenance costs. Using it as a coating can greatly protect the coated substrate. In addition, liquid fluororubber has a certain linear structure, which can store the stress generated by the curing of the coating and dissipate it, thereby solving the problem that a large amount of internal stress generated by the curing of the coating cannot be dissipated.

[0011] Epoxy acrylic resin polymer: Fluororubber has poor adhesion to metal. The functional groups brought by epoxy resin of epoxy acrylate can improve the adhesion of fluororubber before and after curing. In addition, epoxy acrylic resin polymer has more reactive functional groups and will continue to cross-link after curing, thereby improving the hardness of the coating.

[0012] Mesoporous tungsten carbide functionalized with nano-graphene: The structure of nano-graphene is similar to that of graphene. As a sheet structure, both materials have good barrier properties, and both materials are resistant to acid and alkali. The difference from graphene is that graphene contains acetylenic bonds, which can generate free radicals under certain conditions (such as Figure 2As shown), it is cross-linked with a resin or fluororubber that also contains free radicals. Tungsten carbide is a compound composed of tungsten and carbon. It is a black hexagonal crystal with a hardness similar to that of diamond. It is also resistant to strong acids and alkalis. Adding it to the coating can greatly improve the hardness and impact resistance of the coating. Mesoporous materials are a type of porous material with a pore size between 2-50nm. When applied to the coating, they can slow down the speed at which corrosion particles reach the metal matrix. When added in high amounts, they can also absorb corrosion particles. Mesoporous tungsten carbide has the advantages of both of the above, and the existence of this pore size provides the necessity for nano-graphene to enter the pore. The coating inside the tank may face problems such as workers entering the tank to clean it, and their shoes or tools may damage the coating to a certain extent. Therefore, the coating is required to have a certain hardness. Tungsten carbide is often added to the coating in the prior art to improve the hardness of the coating. However, tungsten carbide, as an inorganic material, is difficult to disperse evenly when added to the organic coating, and will precipitate during the construction and curing process, resulting in no tungsten carbide on the coating surface, and the hardness of the coating cannot be improved. The present invention selects mesoporous tungsten carbide with a pore size that can pass through nano-graphene. During the free radical polymerization growth and cross-linking process of graphene, the tungsten carbide is fixed in series by graphene, which solves the problem of inorganic material precipitate, thereby improving the hardness of the coating (such as Figure 1 as shown).

[0013] In addition, graphyne and epoxy acrylic resin copolymers improve the alkali resistance of fluororubber to a certain extent. Epoxy acrylic resin polymers do not react with alkali, graphyne does not react with alkali, and has a layered structure, which blocks the penetration of hydroxide ions, so that the fluororubber coating can be applied to alkaline solutions with higher concentrations. When used as the inner coating of transport containers, it can contain more types of corrosive media.

[0014] In the above technical scheme, the triple bonds in graphyne, the double bonds in fluororubber, and the double bonds in epoxy acrylic resin polymer can undergo free radical polymerization, so that the three are not simply physically blended, but form an integrated coating material, which can avoid the occurrence of precipitation, agglomeration, uneven dispersion and the like, thereby avoiding the degradation of mechanical properties and corrosion resistance caused by uneven material properties.

[0015] Specifically, the preparation method of the nano-graphene functionalized mesoporous tungsten carbide includes the following steps: dispersing nano-graphene in an organic solvent, then adding mesoporous tungsten carbide, using a cell crusher to vibrate for 0.5-1h under 1000-1500W conditions, and finally drying to obtain nano-graphene functionalized mesoporous tungsten carbide; wherein the weight ratio of the nano-graphene to the mesoporous tungsten carbide is (0.045-0.0625): (0.015-0.0375), and the particle size of the nano-graphene is smaller than the pore size of the mesoporous tungsten carbide.

[0016] In the above technical solution, a cell crusher is used to provide vibration with sufficient power so that nano-graphene can better penetrate into the pores of mesoporous tungsten carbide, so that during the graphene free radical polymerization growth cross-linking process, the tungsten carbide is fixed in series by the graphene. The organic solvent is preferably isopropanol.

[0017] Preferably, the particle size of the nano-graphene is 30-40 nm, and the pore size of the mesoporous tungsten carbide is 40-50 nm, so as to improve the dispersion performance while ensuring that the tungsten carbide is fixed in series by the graphene.

[0018] Preferably, the dispersion conditions are: 150-200W ultrasonic dispersion for 1-2h, so that the nano-graphene is evenly dispersed to facilitate subsequent reactions.

[0019] The drying condition is: using a rotary evaporator to spin dry for 6-8 hours. The purpose of spin drying is to dry, and the advantage of using a spin dryer is that the dried nanomaterials have less agglomeration.

[0020] Preferably, the viscosity of the epoxy acrylic resin oligomer is 2000-3000 cps and the molecular weight is 500-2000; the purpose of selecting low molecular weight and low viscosity epoxy acrylic resin oligomer is to improve the alkali resistance of fluororubber and enhance the adhesion of fluororubber coating.

[0021] Specifically, the preparation method of the liquid fluororubber includes the following steps: dissolving fluororubber with a molecular weight of 1000-2000, adding an alkaline solution, standing at 40-45°C to generate double bonds, then washing, drying, and then adding a monofunctional acrylate monomer that is 1-3 times the weight of the fluororubber after drying.

[0022] In the above technical solution, the fluororubber material is treated with heating alkali to remove hydrogen fluoride, and a diluent monofunctional acrylate monomer is added to obtain a liquid fluororubber containing double bonds. The solvent of the fluororubber can be acetone or ethyl acetate. The alkaline solution can be KOH, NaOH, etc., and the mass concentration is preferably 8-12%.

[0023] On the one hand, the monofunctional acrylate monomer acts as a diluent for fluororubber, making the fluororubber fluid and easy to coat. On the other hand, the monofunctional acrylate monomer has a linear structure in free radical polymerization and is not branched, which to a certain extent solves the stress concentration problem caused by excessive cross-linking (such as Figure 2 as shown).

[0024] Preferably, the blending is carried out by thermomechanical stirring at a stirring speed of 200-350 r / min and a temperature of 35-85°C.

[0025] The viscosity of liquid fluororubber is lower than that of epoxy acrylic resin. Therefore, in the preparation process of the coating, nano-graphene functionalized mesoporous tungsten carbide is first dispersed in the liquid fluororubber and then mixed with the epoxy acrylic resin. Because the viscosity of liquid fluororubber is lower than that of epoxy acrylic resin, nano-graphene functionalized mesoporous tungsten carbide is relatively easy to disperse.

[0026] The second aspect of the present invention provides an acid- and alkali-resistant coating obtained by the above-mentioned preparation method.

[0027] The third aspect of the present invention provides an acid- and alkali-resistant coating, which is obtained by coating, irradiating, cross-linking and curing the above-mentioned acid- and alkali-resistant coating.

[0028] Radiation cross-linking uses high-energy electron beams generated by electron irradiation accelerators to bombard the insulating layer and sheath, breaking the polymer chain. Each breakpoint becomes a free radical. The free radicals are unstable and need to recombine with each other. After recombination, the original chain molecular structure becomes a three-dimensional network molecular structure to form a cross-link. Applying it to coating curing technology can quickly complete curing, with low energy consumption, no VOC volatilization, and high efficiency.

[0029] During the irradiation process of the above-mentioned coating, the triple bonds in graphyne, the double bonds in fluororubber, and the double bonds in epoxy acrylic resin can be better free radical polymerized to form an integrated coating material.

[0030] Preferably, the irradiation dose is 20-60 kGy, the irradiation is performed 1-3 times, the irradiation time is 0.2-1 s, and the irradiation interval time is 2-3 s.

[0031] Preferably, the coating has a thickness of 40-60 μm.

[0032] A fourth aspect of the present invention provides a use of the above-mentioned acid- and alkali-resistant coating in preparing an inner wall coating of a transport container.

[0033] As an embodiment, the inner wall of the transport container is made of carbon steel, and the application method is: firstly, the inner wall of the container is sandblasted and passivated with a passivation liquid, then the acid and alkali resistant coating is applied to the inner wall of the container, and finally, radiation cross-linking and curing is performed.

[0034] The purpose of sandblasting is to provide roughness to metal materials and to provide bonding sites during paint spraying, painting, and gelling.

[0035] Specifically, the passivation solution includes KH-570 with a mass concentration of 18-20%, and fluorozirconic acid or fluorotitanic acid with a mass concentration of 0.7-4%.

[0036] Fluozirconic acid or fluorotitanic acid can react with metal materials to etch and generate products such as zirconium oxide and titanium oxide, thereby improving the metal's corrosion resistance and providing a certain degree of roughness for the metal material. This improves its bonding with the coating and uses an amphiphilic silane coupling agent, which combines with a metal-based inorganic body at one end and with an organic body such as a resin at the other end. Double bonds are generated under irradiation and react with free radicals in the coating, greatly enhancing the bonding between the metal and the coating and improving the adhesion of fluororubber.

[0037] Preferably, the coating thickness of the acid- and alkali-resistant coating is 30-50 μm.

[0038] Preferably, the conditions for the radiation cross-linking and curing are: radiation dose of 30-70 kGy, 2-3 irradiations, irradiation time of 0.5-1 s, and irradiation interval time of 1-2 s.

[0039] Different coating thicknesses use different irradiation doses and irradiation times, which need to be adjusted according to factors such as process and film thickness. Since the inner surface of the tank has been passivated, the anti-corrosion ability of the tank has been improved, the coating thickness is reduced to a corresponding extent, and the corresponding irradiation parameters are adjusted.

[0040] Through the above technical solution, the present invention achieves the following beneficial effects:

[0041] 1. In the present invention, fluororubber has good sealing performance and can protect the coated substrate to a great extent; the functional groups brought by the epoxy resin of epoxy acrylate can improve the adhesion of fluororubber before and after curing; Graphene itself has barrier ability, which increases the anti-corrosion effect to a certain extent and resists the penetration of corrosive media. It is combined with resin and rubber in the form of free radical polymerization, which improves the dispersion ability of Graphene between the two, so that the overall anti-corrosion ability of the coating material is improved; mesoporous tungsten carbide can greatly improve the hardness and impact resistance of the coating. The present invention selects mesoporous tungsten carbide with an aperture that can pass through nanographene. In the process of graphene free radical polymerization growth and cross-linking, tungsten carbide is fixed in series by graphene, solving the problem of inorganic material precipitation. The triple bonds in graphyne, the double bonds in fluororubber, and the double bonds in epoxy acrylic resin oligomers can be subjected to free radical polymerization, so that the three are not simply physically blended, but form an integrated coating material, which can avoid the occurrence of coagulation, agglomeration, uneven dispersion, etc., thereby avoiding the decrease in mechanical properties and anti-corrosion properties caused by uneven material properties. The coating of the present invention has low VOC emissions during construction, light coating quality, and can be used in multiple anti-corrosion fields such as acid and alkali.

[0042] 2. In a preferred technical solution of the present invention, during the preparation of the coating, nano-graphene-functionalized mesoporous tungsten carbide is first dispersed in liquid fluororubber and then mixed with epoxy acrylic resin. This is because the viscosity of liquid fluororubber is lower than that of epoxy acrylic resin and it is relatively easy to disperse.

[0043] 3. When the coating of the present invention is prepared as a coating, it is cured by radiation cross-linking technology. During the irradiation process, the triple bonds in graphyne, the double bonds in fluororubber, and the double bonds in epoxy acrylic resin can be better free radical polymerized to form an integrated coating material.

[0044] 4. When the coating of the present invention is used for a container made of carbon steel, the inner wall of the container is firstly subjected to sandblasting and passivation treatment with a passivation liquid, and then the acid-alkali resistant coating is applied to the inner wall of the container, and finally irradiated for cross-linking and curing. The passivation operation improves the anti-corrosion ability of the metal while providing a certain roughness for the metal material, thereby improving its bonding strength with the coating. Moreover, the passivation liquid generates double bonds under irradiation, reacts with free radicals in the coating, greatly improving the bonding strength between the metal and the coating, and improving the adhesion problem of fluororubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a schematic diagram of radiation cross-linking of nano-graphene functionalized mesoporous tungsten carbide in the present invention;

[0046] Figure 2 This is a schematic diagram of free radical generation by irradiation in the present invention;

[0047] Figure 3 It is a flow chart of the preparation of coatings and coatings in the embodiments of the present invention.

[0048] Description of Reference Numerals

[0049] 1-nanographene, 2-mesoporous tungsten carbide, 3-nanographene functionalized mesoporous tungsten carbide, 4-nanographene functionalized mesoporous tungsten carbide after free radical polymerization, 5-alkali-treated fluororubber, 6-epoxy acrylate, 7-graphene, 5'-alkali-treated fluororubber that generates free radicals after irradiation, 6'-epoxy acrylate that generates free radicals after irradiation, 7'-graphene that generates free radicals after irradiation. DETAILED DESCRIPTION

[0050] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0051] In the following examples, reagents were all purchased from the market, and the specific information is as follows:

[0052] Nano-graphene was purchased from Suzhou Kaifa New Materials Technology Co., Ltd.;

[0053] Isopropanol, acetone, ethyl acetate, fluoroacetic acid, and fluorotitanic acid were purchased from Aladdin Reagent (analytical grade);

[0054] Mesoporous tungsten carbide was purchased from China Tungsten Online Technology Co., Ltd.;

[0055] Fluororubber and liquid fluororubber were purchased from Daikin, Japan;

[0056] Monofunctional acrylate monomer was purchased from Sartomer (analytical grade);

[0057] Epoxy acrylic resin oligomer was purchased from Sartomer (analytical grade).

[0058] The equipment models are as follows:

[0059] Ultrasonic instrument: Qingdao Jingcheng Instrument Co., Ltd. (200W);

[0060] Cell crusher: Beijing Jingmeirui Technology Co., Ltd. (SCIENTZ-4TD);

[0061] Electron irradiation accelerator: CGN Dasheng Accelerator Technology Co., Ltd. (low energy).

[0062] Example 1

[0063] like Figure 3 As shown, the preparation process is as follows:

[0064] S1, take 30 parts of graphyne with a particle size of about 30nm and add them to 100 parts of isopropanol solution, use a 150W ultrasonic instrument to disperse for 1h, then add 10 parts of mesoporous tungsten carbide with a pore size of about 40nm to the solution, use a 1000W cell crusher to vibrate for 0.5h, and then use a rotary evaporator to spin dry for 6h to obtain nano-graphyne functionalized mesoporous tungsten carbide;

[0065] S2, take 50 parts of fluororubber with a molecular weight of about 1000, add 200 parts of acetone solution, treat with 10 parts of 8% KOH solution, stand at 40°C to generate double bonds, wash, dry, and then add 1 times the weight of monofunctional acrylate monomer after drying to obtain liquid fluororubber;

[0066] S3, adding 3 parts of nano-graphene functionalized mesoporous tungsten carbide to 100 parts of liquid fluororubber and dispersing them evenly, and then adding 50 parts of epoxy acrylic resin polymer with a viscosity of about 2000cps and a molecular weight of about 500, and preparing an acid-alkali resistant coating by a thermomechanical stirring method at a stirring speed of 200r / min and a temperature of 35°C for standby use;

[0067] S4. The inner wall of the tank truck whose material is carbon steel 235 is sandblasted, and after sandblasting, it is treated with a passivation solution mixed with 20% KH-570 and 8% fluorochloric acid in a mass ratio of 1:0.1. The treated carbon steel is coated with acid- and alkali-resistant coating with a coating thickness of 50μm. The irradiation dose is 30kGy, irradiated twice, with an irradiation interval of 1s and an irradiation time of 0.5s for cross-linking and curing to obtain an acid- and alkali-resistant transport tank.

[0068] Example 2

[0069] S1, take 50 parts of Graphene with a particle size of about 40nm and add them to 200 parts of isopropanol solution, use a 200W ultrasonic instrument to disperse for 2h, then add 30 parts of mesoporous tungsten carbide with a pore size of about 50nm to the solution, use a 1500W cell crusher to vibrate for 1h, and then use a rotary evaporator to spin dry for 8h to obtain nano-graphene functionalized mesoporous tungsten carbide;

[0070] S2, take 50 parts of fluororubber with a molecular weight of about 2000, add 500 parts of ethyl acetate solution, treat with 20 parts of 12% NaOH solution, stand at 45°C to generate double bonds, wash, dry, and then add 3 times the weight of the dried fluororubber monofunctional acrylate monomer to obtain liquid fluororubber;

[0071] S3, adding 2.5 parts of nano-graphene functionalized mesoporous tungsten carbide to 100 parts of liquid fluororubber and dispersing them evenly, and then adding 25 parts of epoxy acrylic resin polymer with a viscosity of about 3000cps and a molecular weight of about 2000, and preparing an acid-alkali resistant coating by a thermomechanical stirring method at a stirring speed of 350r / min and a temperature of 85°C for standby use;

[0072] S4. The inner wall of the tank truck whose material is carbon steel 245 is sandblasted, and after sandblasting, it is treated with a passivation liquid mixed with 30% KH-570 and 12% fluorotitanic acid in a mass ratio of 1:0.5. The treated carbon steel is coated with acid and alkali resistant coating with a coating thickness of 30μm. The irradiation dose is 70kGy, irradiated 3 times, irradiated for 2s, and irradiated for 1s to cross-link and cure, so as to obtain an acid and alkali resistant transport tank.

[0073] Example 3

[0074] S1, take 40 parts of Graphene with a particle size of about 35nm and add them to 150 parts of isopropanol solution, use a 175W ultrasonic instrument to disperse for 1.5h, then add 20 parts of mesoporous tungsten carbide with a pore size of about 45nm to the solution, use a 1250W cell crusher to vibrate for 45min, and then use a rotary evaporator to spin dry for 7h to obtain nano-graphene functionalized mesoporous tungsten carbide;

[0075] S2, take 70 parts of fluororubber with a molecular weight of about 1500, add 350 parts of ethyl acetate solution, treat with 15 parts of 10% KOH solution, stand at 40°C to generate double bonds, wash, dry, and then add monofunctional acrylate monomer twice the weight of the dried fluororubber to obtain liquid fluororubber;

[0076] S3, adding 4 parts of nano-graphene functionalized mesoporous tungsten carbide to 150 parts of liquid fluororubber and dispersing them evenly, and then adding 50 parts of epoxy acrylic resin polymer with a viscosity of about 2500cps and a molecular weight of about 1500, and preparing an acid-alkali resistant coating by a thermomechanical stirring method at a stirring speed of 275r / min and a temperature of 60°C for standby use;

[0077] S4. The inner wall of the tank truck whose material is carbon steel 345 is sandblasted, and after sandblasting, it is treated with a passivation solution mixed with 25% KH-570 and 10% fluorinated acid in a mass ratio of 1:0.25. The treated carbon steel is coated with acid and alkali resistant coating with a coating thickness of 50μm. The irradiation dose is 50kGy, irradiated twice, with an irradiation interval of 2s and an irradiation time of 0.8s for cross-linking and curing to obtain an acid and alkali resistant transport tank.

[0078] Example 4

[0079] Other conditions are the same as those in Example 3, except that commercially available liquid fluororubber is used.

[0080] Comparative Example 1

[0081] Other conditions are the same as those in Example 3, except that the mesoporous tungsten carbide functionalized with nano-graphene is omitted.

[0082] Comparative Example 2

[0083] Other conditions are the same as those in Example 3, except that in step S4, the inner wall of the transport tank is not passivated.

[0084] Comparative Example 3

[0085] Other conditions are the same as those in Example 3, except that a fluororubber coating on the market is used instead of the acid- and alkali-resistant coating in Example 3.

[0086] Performance Testing

[0087] 1. Corrosion resistance test

[0088] In order to verify the medium corrosion resistance of the acid-base resistant transport tank, the transport tank treated by the methods of the above Examples 1-4 and Comparative Examples 1-3 was tested. The corrosive medium accounting for 80% of the volume of the tank was filled and the tank was continuously heated at 40°C (equivalent to accelerated aging). After immersion for 2 months, the coating condition was observed. The results are shown in Table 1. In the table, "√" indicates that the coating is intact, and "×" indicates that the coating is corroded.

[0089] Table 1 Corrosion resistance test

[0090]

[0091] Due to its sealing and corrosion resistance, fluororubber coatings will undergo dehydrofluorination when exposed to alkaline materials. If the material is heated or contains other oxidizing components, the double bonds will further react to generate other products, break the molecular chain, and render the material ineffective. From the results in Table 1, it can be seen that when exposed to 35% sodium hydroxide at a high temperature of 40°C, Examples 1-4 can meet the requirements, while Comparative Example 1, which lacks nano-graphene functionalized mesoporous tungsten carbide, cannot meet the requirements, proving that the flaky graphene can effectively block the further penetration of hydroxide ions.

[0092] 2. Adhesion test

[0093] To verify the adhesion of the acid- and alkali-resistant transport tank coating, the coatings prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to a puller pull test and a pencil hardness test on a carbon steel 345 surface with a length and width of 5 cm×5 cm. The results are shown in Table 2.

[0094] Table 2 Adhesion test

[0095]

[0096] It can be seen from Table 2 that the passivation treatment significantly improves the adhesion between the fluororubber coating and carbon steel. The improvement effect of Examples 1-4 using the passivation treatment and epoxy acrylic resin copolymer is more obvious, which greatly improves the adhesion performance of the paint film.

[0097] With the increase of tungsten carbide content, the hardness of the coating is significantly improved. The reason why the hardness of the comparative example 1 without tungsten carbide is still higher than that of the fluororubber coating on the market is that the epoxy acrylic resin polymer is tightly combined with the fluororubber during the cross-linking and curing process, the degree of cross-linking is high, and the hardness increases.

[0098] The preferred implementation modes of the present invention are described in detail above in combination with the embodiments; however, the present invention is not limited to the specific details in the above implementation modes. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical scheme of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0099] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0100] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing an acid- and alkali-resistant coating, characterized in that: The method comprises the following steps: mixing liquid fluororubber, epoxy acrylic resin oligomer and nano-graphene functionalized mesoporous tungsten carbide in a weight ratio of (2-4): 1: (0.06-0.1) to obtain the nano-graphene functionalized mesoporous tungsten carbide. The method comprises the following steps: dispersing nano-graphene in an organic solvent, then adding mesoporous tungsten carbide, vibrating the mixture at 1000-1500W for 0.5-1h by using a cell crusher, and finally drying the mixture to obtain the nano-graphene functionalized mesoporous tungsten carbide. Mesoporous tungsten carbide; wherein the weight ratio of the nano-graphene to the mesoporous tungsten carbide is (0.045-0.0625): (0.015-0.0375), and the particle size of the nano-graphene is smaller than the pore size of the mesoporous tungsten carbide, the particle size of the nano-graphene is 30-40nm, and the pore size of the mesoporous tungsten carbide is 40-50nm; the dispersion conditions are: 150-200W ultrasonic dispersion for 1-2h; the drying conditions are: using a rotary evaporator for spin drying for 6-8h; The preparation method of the liquid fluororubber comprises the following steps: dissolving fluororubber with a molecular weight of 1000-2000, adding an alkaline solution, standing at 40-45° C. to generate double bonds, then washing, drying, and then adding a monofunctional acrylate monomer in an amount of 1-3 times the weight of the dried fluororubber to obtain the liquid fluororubber.

2. The method for preparing the acid- and alkali-resistant coating according to claim 1, characterized in that: The epoxy acrylic resin oligomer has a viscosity of 2000-3000 cps and a molecular weight of 500-2000.

3. The method for preparing the acid- and alkali-resistant coating according to any one of claims 1 to 2, characterized in that: The blending conditions are: adopting a thermomechanical stirring method, a stirring speed of 200-350 r / min, and a temperature of 35-85°C.

4. Acid- and alkali-resistant coating obtained by the preparation method according to any one of claims 1 to 3.

5. An acid- and alkali-resistant coating, characterized in that: The acid and alkali resistant coating according to claim 4 is obtained by coating, irradiating, cross-linking and curing.

6. The acid- and alkali-resistant coating according to claim 5, characterized in that: The irradiation dose is 20-60 kGy, irradiation is 1-3 times, irradiation time is 0.2-1 s, and irradiation interval time is 2-3 s; and / or The coating thickness is 40-60 μm.

7. Use of the acid- and alkali-resistant coating according to claim 4 in preparing inner wall coatings of transport containers.

8. The use according to claim 7, characterized in that: The inner wall of the transport container is made of carbon steel, and the application method is: firstly, the inner wall of the container is subjected to sandblasting and passivation liquid passivation treatment, then the acid and alkali resistant coating is applied to the inner wall of the container, and finally, radiation cross-linking and curing is performed.

9. The use according to claim 8, characterized in that: The passivation solution comprises KH-570 with a mass concentration of 18-20% and fluorozirconic acid or fluorotitanic acid with a mass concentration of 0.7-4%; and / or The coating thickness of the acid- and alkali-resistant coating is 30-50 μm; and / or The conditions for the radiation cross-linking and curing are: radiation dose of 30-70 kGy, 2-3 irradiations, 0.5-1 s irradiation time, and 1-2 s irradiation interval time.

Citation Information

Patent Citations

  • Chemical resistance

    GB202206307D0